Improving Students' Mathematical Problem Solving Ability in Trigonometry Material Using the Flipped Classroom Model - Ma'ruf, Abdul Hakim; Triyono, Ageng; Ismail, Muhammad Rifki (Journal of Instructional Mathematics, 2023)
This research was motivated by the relatively low learning outcomes and problem solving abilities of class IX students. So this research aims to improve learning outcomes and improve students' mathematical problem solving abilities. The objectives were achieved through the classroom action research method by applying the flipped classroom model for 3 cycles in trigonometry learning. This research involved 32 students from SMA N 1 Pedes. Data was collected using test instruments, observation sheets, and interviews. Data were analyzed using the Miles & Hubberman method. The results of the analysis show an increase in learning outcomes and an increase in mathematical problem solving abilities. The increase in learning outcomes is shown by the average value in cycle I of 67.28, cycle II of 72.97, and cycle III of 75.41. The percentage of mathematical problem solving ability from cycle I was 47%, increasing in cycle II to 71.87%; and in cycle III it was 84.37%. Thus, student learning outcomes have reached the specified criteria of 74, and meet the criteria for the percentage of problem solving ability set at 80%. So the application of the flipped classroom model can be recommended for further use in mathematics learning, especially trigonometry.